2021
DOI: 10.47631/jsrmbs.v2i1.218
|View full text |Cite
|
Sign up to set email alerts
|

Management Analysis of Infection Prevention: Nurses’ Compliance in Implementing Hand Hygiene in the Inventories of Rantauprapat Hospital

Abstract: Purpose: This study aims to analyze infection control prevention management on nurses' compliance in implementing hand hygiene in the in-patient rooms of Rantauprapat Hospital. Methods: An analytical survey was employed with a cross-sectional design. The population included the nurses who served in the in-patient rooms of Regional General Hospital (RSUD) Rantauprapat with a sample of 64 participants. The data was collected using purposive sampling. For data analysis, univariate, bivariate analysis with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of the study from Shahrbabaki, et al stated that the workload, lack of knowledge and wrong behavior patterns and not yet optimal management such as planning, training, and lack of availability of equipment were obstacles to handwashing for health workers including nurses in the Intensive Care room, have not awareness in preventing infection which can result in increased costs [27]. In line with research from Daulay, Sudiro, dan Amirah that in supporting the implementation of handwashing, it is necessary to contribute from management, namely supervision and providing training, so that 45.3% of infection control management is in the insufficient category [28].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study from Shahrbabaki, et al stated that the workload, lack of knowledge and wrong behavior patterns and not yet optimal management such as planning, training, and lack of availability of equipment were obstacles to handwashing for health workers including nurses in the Intensive Care room, have not awareness in preventing infection which can result in increased costs [27]. In line with research from Daulay, Sudiro, dan Amirah that in supporting the implementation of handwashing, it is necessary to contribute from management, namely supervision and providing training, so that 45.3% of infection control management is in the insufficient category [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results showed that the percentage of healthcare providers and physicians following various IPC measures was ranged from 31% (wearing personal protective equipment) to 97% (washing and cleaning hands constantly). Recently, Daulay and co -workers conducted a study to examine the impact of infection control and prevention management on the compliance of nurses in adopting hand hygiene in Rantauprapat Hospital's in-patient rooms [17]. The results revealed a relationship between infection control and prevention management and nurses' compliance in adopting hand hygiene in Rantauprapat Hospital's in-patient rooms.…”
mentioning
confidence: 99%